A novel protein encoded by circUBE2G1 suppresses glycolysis in gastric cancer through binding to ENO1 - Lu Lu; Guoqing Guo; Jiahao Guo; Hanyang Li; Kexin Chen; Yuli Chen; Qiuhui Li; Qiunuo Li; Yuhao Diao; Ming Sun; Hao Wu; Xianghua Liu (Cell Death Discovery)
Abstract Gastric cancer (GC), a malignant neoplasm originating in the stomach epithelium, is characterized by substantial global incidence and mortality rates, posing a substantial threat to public health systems worldwide. The present study was designed to identify and validate a previously unannotated protein encoded by circular RNA (circRNA), with the principal objective of elucidating its functional significance and mechanistic basis in gastric carcinogenesis.CircUBE2G1 (hsa_circ_003239) was identified as a translationally active circRNA exhibiting significant downregulation in gastric cancer. The novel protein product derived from circUBE2G1 translation, designated circUBE2G1-99aa, was confirmed through co-immunoprecipitation coupled with tandem mass spectrometry (LC-MS/MS), representing the first documentation of its existence in human malignancies.CircUBE2G1-99aa exhibited marked downregulation in gastric cancer (GC), with its diminished expression levels demonstrating significant correlations with larger primary tumor size, lymph node metastasis, and advanced TNM stages. Functionally, circUBE2G1 exerted tumor-suppressive effects via its encoded protein circUBE2G1-99aa, not the full-length RNA, by inhibiting GC cell proliferation in vitro and in vivo. Mechanistically, circUBE2G1-99aa directly bound ENO1 and suppressed its glycolytic activity, thereby reducing glycolysis in GC cells. These findings delineate the functional and mechanistic landscape of circUBE2G1-99aa in gastric cancer, proposing its dual utility as both a prognostic biomarker and therapeutic target in clinical oncology.